Pengaruh Metode Outdoor Learning Terhadap Hasil Belajar Ipa - Amalia Fathul Hidayah, Putri Febiyani Tri (Prosiding University Research Colloquium, 2021)
This study aims to determine the effect of the outdoor learning method on science learning outcomes for 4th grade students of SD Negeri Rejowinangun 6 Uatra. This study uses a comparison method of pre-test and post-test results. Subjects in this study were taken randomly. The sample in this study found 12 students. The results showed that there was a positive influence from the use of outdoor learning methods on science learning outcomes for Grade 4. This was evidenced by the average pre-test result of 61.47 and the post-test score of 92.00.